The Effect of Product Innovation and Promotion on Purchase Decisions at Consumers of Mc Donald's Margonda Depok - Shelly Rosa Damayanti, Shelly Rosa Damayanti; Robert Siregar; Nurminingsih; Ahmadun (LPPM Universitas Respati Indonesia, 2023)
This study aims to determine and analyze the influence of product innovation and promotion on purchasing decisions at Mc Donald's Margonda Depok consumers. This research method is a quantitative research, this research was conducted at Mc Donald's Margonda Depok. The population in this study were all Mc Donald's customers who were or had eaten at Mc Donald's Margonda Depok. With a sample of 120 respondents. Data analysis was based on using the SPSS program version 26.0 for Windows. The results of this study are Product Innovation has an effect on Purchasing Decisions, Promotion has an effect on Purchase Decisions, Product Innovation and Promotions together have an effect on Purchasing Decisions. Keywords: Product Innovation, Promotion, Purchase Decision